Regulatory Enforcement and Restoration: Natural Resource Maintenance for Indonesia's Sustainable Economy - Muslikhun, Muslikhun (DAS Institute, 2024)
Regulation and restoration of natural resources are important components in supporting the sustainability of the Indonesian economy. This paper discusses environmental policies and restoration efforts implemented by the government, and their impacts on ecosystem maintenance and long-term economic growth. Using a multidisciplinary approach, this paper aims to review studies of forest restoration policies and water resource management that have been implemented in Indonesia, as well as comparisons with other countries. Strong regulation and community-based restoration can increase economic productivity and conserve natural resources (Silvestri, S., & C. F., 2016).). This paper concludes that integrated management of natural resources is needed to achieve a sustainable economy and social welfare of the nation